Distinct DNA methylation epigenotypes in bladder cancer from different Chinese sub-populations and its implication in cancer detection using voided urine - Tong Joanna HM; Huang Martin MS; Tung Chun-Liang; Chen Gary CW; Huang Wei; Wang Xiaoling; Chen Yanning; Ng Chi-Fai; Jou Yeong-Chin; Yip Sidney KH; Tsai Ming-Hsuan; Chen Pi-Che; et al. (BMC, 2011)
Abstract Background Bladder cancer is the sixth most common cancer in the world and the incidence is particularly high in southwestern Taiwan. Previous studies have identified several tumor-related genes that are hypermethylated in bladder cancer; however the DNA methylation profile of bladder cancer in Taiwan is not fully understood. Methods In this study, we compared the DNA methylation profile of multiple tumor suppressor genes (APC, DAPK, E-cadherin, hMLH1, IRF8, p14, p15, RASSF1A, SFRP1 and SOCS-1) in bladder cancer patients from different Chinese sub-populations including Taiwan (104 cases), Hong Kong (82 cases) and China (24 cases) by MSP. Two normal human urothelium were also included as control. To investigate the diagnostic potential of using DNA methylation in non-invasive detection of bladder cancer, degree of methylation of DAPK, IRF8, p14, RASSF1A and SFRP1 was also accessed by quantitative MSP in urine samples from thirty bladder cancer patients and nineteen non-cancer controls. Results There were distinct DNA methylation epigenotypes among the different sub-populations. Further, samples from Taiwan and China demonstrated a bimodal distribution suggesting that CpG island methylator phentotype (CIMP) is presented in bladder cancer. Moreover, the number of methylated genes in samples from Taiwan and Hong Kong were significantly correlated with histological grade (P < 0.01) and pathological stage (P < 0.01). Regarding the samples from Taiwan, methylation of SFRP1, IRF8, APC and RASSF1A were significantly associated with increased tumor grade, stage. Methylation of RASSF1A was associated with tumor recurrence. Patients with methylation of APC or RASSF1A were also significantly associated with shorter recurrence-free survival. For methylation detection in voided urine samples of cancer patients, the sensitivity and specificity of using any of the methylated genes (IRF8, p14 or sFRP1) by qMSP was 86.7% and 94.7%. Conclusions Our results indicate that there are distinct methylation epigenotypes among different Chinese sub-populations. These profiles demonstrate gradual increases with cancer progression. Finally, detection of gene methylation in voided urine with these distinct DNA methylation markers is more sensitive than urine cytology.